F46 Relationship between distinct motor symptoms and apathy in huntington's disease: clues to mechanism. (September 2018) - Nair, Akshay; Aziz, N Ahmad; Rutledge, Robb; Rees, Geraint; Tabrizi, Sarah J
Abstract : Introduction: Disrupted gating of motor control through striatal pathways is thought to drive the development of motor symptoms in Huntington's disease (HD). The range of motor symptoms, from chorea to bradykinesia, is thought to be driven by disruption in different striatal pathways. Aside from motor control, striatal pathways are also thought to play a key role in the expression of motivated behaviour. On this basis we asked whether the association between apathy and specific motor symptoms is in keeping with the hypothesis that apathy in HD is another manifestation of dysfunctional striatal gating. Methods: Clinical data on 2608 patients with manifest HD disease was retrieved from the ENROLL-HD database. A linear mixed model was built to assess the relationship between motor symptoms and apathy (measured using the PBA and square root transformed) controlling for cognitive impairment, depression, medication use, disease duration, CAG repeat size and age. In a separate analysis the bradykinesia item was replaced by voluntary finger tapping performance. Results: Although both bradykinesia and chorea were significantly associated with apathy, their effects were in opposite directions. Bradykinesia was associated with greater apathy (β=0.14, p<0.001) whereas chorea was associated with lower apathy (β=−0.12, p<0.001). By comparison rigidity had no significant effect in this large cohort (β=−0.04, p=0.08). In a similar model, slower finger tapping performance was also associated with greater apathy (β=0.07, p=0.001). Depression, medication use and cognitive slowing were also associated with apathy. Conclusion: This analysis suggests that the processes driving distinct motor symptoms in HD may also underlie hard-to-treat psychiatric symptoms such as apathy. A common substrate and likely target for this shared mechanism is the disruption of specific striatal pathways that gate actions, decisions and motivated behaviour.